Chaetomium siamense sp. nov., a soil isolate from Thailand, produces a new chaetoviridin, G - Chaninun Pornsuriya; Kasem Soytong; Supattar Poeaim; Somdej Kanokmedhakul; Primmala Khumkomkhet; Fu-Cheng Lin; Hong Kai Wang; Kevin David Hyde (My University, 2011)
Chaetomium siamense sp. nov., isolated from soil in a pineapple plantation in Thailand, is described and illustrated. The new species is similar to C. cupreum in having superficial globose or ovate ascomata with red circinate ascomatal hairs but can be distinguished by its fusiform ascospores with two apical germ pores. Phylogenetic analysis of ITS rDNA sequence data also supports C. siamense as distinct. Investigation of the secondary metabolites of C. siamense led to the isolation of one new (chaetoviridin G) and seven known compounds (ergosterol, 24( R )-5α,8α-epidioxyergosta-6-22-diene-3β-ol, ergosterylplamitate, cochliodone D, chaetoviridin A, chaetoviridin F, chrysophanol).
Keywords: Chaetomium; Genomics and Phylogenetic Studies